THE ROLE OF INTERVENTIONAL METHODS IN TREATMENT OF PULMONARY EMBOLISM - N. T. Vatutin; G. G. Taradin; I. V. Kanisheva; D. V. Bort; A. N. Zagorujko (Архивъ внутренней медицины)
The presented review concerns to current interventional methods of acute pulmonary embolism treatment. The article provides a rationale for catheter approaches, detailed description of patient selection and risk stratification including an estimation of thromboembolic burden, risk degree of acute pulmonary embolism, bleeding risk assessment, and patient-specific considerations. The review contains the up-to-date classification of pulmonary embolism on the basis of 30-day mortality assessment and estimation of disease outcome according to the conventional and simplified Pulmonary Embolism Severity Index. A special attention is paid to interventional methods peculiarly, in particular to catheter directed thrombolysis, rheolytic thrombectomy, thrombus fragmentation and aspiration. The results of studies concerning efficiency and safety of endovascular methods in treatment of pulmonary embolism patients are reported. It was emphasized importance of further investigation of various clinical aspects using these methods for obtaining of comprehensive information about treatment of the dangerous disease associated with significant morbidity and mortality.